The impact of viral infections on the results of hemopoietic stem cell transplantation in patients with hematologic malignancies - T. V. Antonova; O. E. Pobegalova; M. S. Nozhkin; M. A. Romanova; O. V. Gorchakova (Журнал инфектологии, 2021)
Study Objective: to assess the impact of herpesviruses infections reactivation and concomitant chronic hepatitis C infection (CHC) on complications and one-year survival after hemopoietic stem cell transplantation (HSCT) in patients with hematologic malignancies.Materials and Methods: medical records of HSCT recipients with PCR-confirmed viral infections (CMV, HHV-6, EBV, HSV-1,2, HCV) from Raisa Gorbacheva Memorial Research Institute for Pediatric Oncology, Hematology and Transplantation of Pavlov First St.Petersburg State Medical University were analyzed retrospectively. The following groups were composed: patients with herpesviruses infections reactivation (PCR+) without clinical manifestation (n=37), patients with clinically manifest herpesviruses infections (n=21), and patients with CHC (n=28). Control groups were selected using matched samples method from patients with negative test results. HSCT complications rate and one-year survival were compared. Statistical analysis was carried out using SPSS Statistics 22 software.Results: Herpesviruses infections reactivation was revealed in 61,2% of 343 patients. The complications rate across the groups did not differ significantly. One-year survival (Kaplan-Meier) was significantly lower in the groups with herpesviruses infections (PCR+) without clinical manifestation (52,1% vs 73,5%), manifest herpesviruses infections (38,1% vs 75,0%), and CHC (64,3% vs 92,9%) than in the respective control groups. There were no significant differences between the group with reactivation of herpesviruses infections without clinical manifestation and the group with manifest herpesviruses infections.Conclusion: Significant impact of herpesviruses infections, including those without clinical manifestation, and HCH with minor symptoms and normal liver functions on one-year survival in patients with hematologic malignancies justifies wider use of antiviral therapy in patients requiring HSCT.